2018
DOI: 10.1186/s12978-018-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Overview of literature on RMC and applications to Tanzania

Abstract: Respectful maternity care research in Tanzania continues to increase. This is an overview of the literature summarizing research based on the domains which comprise this quality of care indicator, ranging from exploratory and descriptive to quantitative measurements of birth perinatal outcomes when respectful interventions are made. The domains of respectful care are reflected in the seven Universal Rights of Childbearing Women but go further to implicate facility administrators and policy makers to provide su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…The main areas of concern were; lack of working equipment and supplies, space constraints, unclear processes, high workload, lack of commitment from leadership, vague and unfulfilled policies (e.g., free treatment for pregnant women and under-five children), and shortage of qualified staff. These findings are similar to those in several studies from within and in other countries [ 17 , 26 , 30 , 32 , 33 ]. For example, a study in Tanzania reported a lack of partitions between beds and that women shared beds [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The main areas of concern were; lack of working equipment and supplies, space constraints, unclear processes, high workload, lack of commitment from leadership, vague and unfulfilled policies (e.g., free treatment for pregnant women and under-five children), and shortage of qualified staff. These findings are similar to those in several studies from within and in other countries [ 17 , 26 , 30 , 32 , 33 ]. For example, a study in Tanzania reported a lack of partitions between beds and that women shared beds [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…They cited lack of resources and poor leadership as contributing to the bridging of professional ethics and integrity, e.g., lack of screening curtains and private rooms affect privacy and confidentiality during care. Studies in other areas have reported similar findings [ 9 , 17 , 32 ]. These findings imply that environmental factors are essential components that may influence the client’s care.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A second "prong" is that health care practitioners themselves must feel valued and respected by their superiors and must value each other. Recent literature 43,44 points out that the low status of midwives in many health system hierarchies, and organizational cultures of blame and a lack of consideration of midwives as essential health workers, effectively constitutes disrespect and abuse of the midwives themselves. Both caregivers and their patients have the right to dignified treatment.…”
Section: Discussionmentioning
confidence: 99%